Plastic Domestication: Reading Species Stories Through the Framework of Plasticity [Plastyczne udomowienie. Lektura narracji gatunkowych przez pryzmat plastyczności] - Włodarczyk, Justyna (Zoophilologica. Polish Journal of Animal Studies, 2026)
This article examines plasticity as a theoretical lens for analyzing non-human animal narratives, focusing on popular animal fiction from the early twentieth century, especially Jack London’s wolf-dog novels. Plasticity – the capacity of organisms to be shaped by environmental pressures – has historically been used to construct species hierarchies, with dogs, particularly wolf-dogs, portrayed as the most plastic and adaptable. This framing often reinforces their ability to internalize human values, positioning canis familiaris as inherently defined by their bond with humans. While plasticity has traditionally upheld anthropocentric frameworks, this article argues that it also offers a means to challenge them. By reconsidering species stories through plasticity, it becomes possible to disrupt hierarchical assumptions and highlight animal agency within broader multispecies networks. This approach not only repositions dogs as active participants in ecological systems but also provides a methodology for disentangling them from human-centered narratives. It also conceptualizes canids as full-fledged subjects of environmental humanities scholarship.